The Future of Islamic Religious Education in Society 5.0 - Hendra Hendra; Saiful Anwar; Syamsul Arifin; Abdul Haris (JIE (Journal of Islamic Education), 2025)
This study is intended to understand the role, obstacles, and prospects of Islamic religious education in facing the Era of Society 5.0. The approach used in this study is a qualitative Library Research type, referring to articles from national and international levels and current books as data sources. The analysis uses reduction, data display and verification. The study results indicate that in the context of Society 5.0, Islamic religious education has an important role and responsibility in facing significant changes caused by advanced technology. Despite challenges like applying technology in learning and maintaining traditional values, great opportunities must be utilized. Among them are the use of technology to expand the reach of Islamic religious education, collaboration with various parties, such as social and economic institutions, and deepening global understanding of Islam. With the right strategy, Islamic religious education can overcome challenges and take advantage of opportunities in the era of Society 5.0 to provide more contextual and relevant education.